Investasi Cryptocurrency Bitcoin Dalam Teknologi BlockchainMenurut Syariat Islam - Wiwin Muchtar Wiyono (Wijayakusuma Law Review, 2022)
Often the rapid development of the world economy and also Islam is the majority of Indonesian people, asMuslims must understand technology Cryptocurrencies and activities related to these technologies, as well asunderstanding the law in Islamic Sharia are sourced from Hadith and verses of the Koran. Cryptocurrency isvirtual money, digital money, or electronic money that exists in cyberspace and does not have a concrete form ofobject. This cryptocurrency has many kinds, including Litecoin, Monero, Ether, Ripple, Ethereum, Qtum, Dash,Zcash, and Bitcoin. Bitcoin security is protected by Blockchain technology. However, Bitcoin does not have anunderlying asset (underlaying asset) and there is no responsible authority agency, its ownership is anonymous, itsvalue fluctuations are very extreme, and is dominated by the opinion publication factor of the marketing system.That is why the use of Bitcoin in investment and business transactions raises pros and cons among economists andscholars. This study aims to get an overview of Bitcoin technology, especially about Blockchain and the legitimacyof its use in investment and business transactions according to Islamic law. The applied theory used is thebusiness taxonomy of haram lidzatihi and haram lighairihi from the number of scholars reconstructed byAdiwarman Abdul Karim. This research is a literature study. The data sources for this research were taken fromthe Koran, the hadith of the Prophet, classical and contemporary books, as well as from online media sources.From this study, it was found that Bitcoin technology with Blockchain can indeed be recognized as an excellentrevolutionary technology, but its use as an investment instrument contains elements of maysir (betting) and as aninstrument of business transactions contains elements of gharar. Its legal position is haram lighairihi.